Variable within-brood maternal provisioning in newly extruded embryos of Homarus gammarus - Leal, Miguel Costa (2013)
Offspring quality of decapod crustaceans has been widely studied, with special emphasis on the sources of variability determining embryonic and larval quality. Nevertheless, maternal provisioning has commonly been overlooked as a potential source of offspring within-brood variability. In the present study, the existence of variable maternal provisioning was assessed through the analysis of the fatty acid (FA) profile of newly extruded embryos from different regions of the brooding chamber of Homarus gammarus. Significant differences in the FA profile of embryos sampled from different pleopods and sides of the brooding chamber were recorded. Significant deviations of the overall mean of each surveyed female were also observed for essential FA, particularly 20:4n-6, 20:5n-3 and 22:6n-3. Lipid energy available to fuel embryogenesis also varied among embryos sampled from different regions of the brooding chamber. Results suggest variable female investment at oocyte production, which may be amplified during the incubation period of developing embryos by differential lipid catabolism. For the first time, maternal provisioning is evidenced as an additional source for within-brood variability in the FA profile of embryos.